DESAIN LAPORAN KEUANGAN UMKM BERBASIS MICROSOFT EXCEL PADA SUNSHINE LAUNDRY - Ivoletti M. Walukow; Christony Maradesa; Esrie A. N. Limpeleh; Andreuw Pantow (Politeknik Ubaya, 2021)
This study aims to design the financial statements of Sunshine Laundry using the Microsoft Excel application. The research method was descriptive qualitative. Instruments of data collection was down through interview in the form of questions regarding the recording of financial statements. While the data collection instrument with documentation, was done through namely evidence of transactions that occurred in the business. The results of this study indicate that the design of financial statements with Microsoft Excel helps Sunshine Laundry in compiling financial reports in accordance with EMKM accounting standards. The design of financial reports using Microsoft Excel is assisted by data flow diagrams to describe the flow of the system consisting of a menu design sheet, module 1, module 2, price list, transaction list, account type, chart of account, general journal, income statement, and statement of financial position.